Laryngeal Mask Airway for Surfactant Administration Versus Standard Treatment Methods in Preterm Neonates with Respiratory Distress Syndrome: A Systematic Review and Meta-analysis - Al Ali, Roqaia Ayesh; Gautam, Bishal; Miller, Michael R.; Coulson, Sherry; Yuen, Doris (American Journal of Perinatology, 2021)
Objective Laryngeal mask airway (LMA) has emerged as an alternative surfactant delivery method. The effectiveness of this method for the delivery of surfactant is uncertain. A meta-analysis of randomized control trials (RCTs) comparing LMA with standard methods of surfactant delivery for the outcomes of surfactant dose repetition, oxygen requirement, mechanical ventilation, intubation, mortality, bronchopulmonary dysplasia (BPD), and pneumothorax.Study Design Systematic review and meta-analysis of RCTs. Homogeneity between studies was analyzed by using I2 statistics. Risk ratio or mean difference of outcomes was assessed from random effects models. Subgroup analyses were conducted when necessary. Data sources are as follows: Ovid Medline, Embase, and the Cochrane Central Register of Controlled trials from inception till December 2018, bibliographies of identified reviews and trial registries for ongoing studies. RCTs comparing short-term respiratory outcomes in neonates with respiratory distress syndrome who were administered surfactant through an LMA versus standard method of care.Results Six RCTs were identified, enrolling a total of 357 infants. Administering surfactant via LMA was associated with decreased FiO2 requirement (mean difference = 1.82 (95% confidence interval [CI]: −6.01–9.66), decreased intubation (risk ratio [RR] = 0.17; 95% CI: 0.05–0.57), and decreased mechanical ventilation (RR = 0.44; 95% CI: 0.31–0.61). There were no significant differences between groups for death, BPD, or pneumothorax.Conclusion LMA might be an effective alternative method of surfactant delivery; however, further high-quality RCTs with larger sample size and including extreme preterm infants are needed to establish LMA as an alternative technique for surfactant delivery.Key Points
Keywords: surfactant; laryngeal mask airway; preterm; infant; neonatal respiratory; distress syndrome; thin catheter; bronchopulmonary dysplasia